(untitled) (Research, Society and Development, 2024)
Cellulite has a multifactorial etiology and causes significant changes in the subcutaneous layer, including edema, lipodystrophy, and fibrous deviation of the connective tissue. These changes are related to hormonal factors and the presence of inflammatory mediators. In this context, far infrared (FIR) has shown beneficial effects on cellular metabolism and function, increasing the bioavailability of nitric oxide (NO) and Ca2+, and improving blood circulation. This study aimed to evaluate the effects of using pants made of FIR-emitting fabric in women with cellulite. This research was submitted to and approved by the Research Ethics Committee. Sixteen sedentary women aged 30 to 55 years, with grade 1 to 4 cellulite were selected. The participants received two pants made of FIR-emitting fabric, INFUSION technology (BEAUTYTECH®, Guariba, SP, Brazil). The pants were worn for a period of 6 hours a day (8:00 a.m. to 6:00 p.m.), 5 times a week, for one month. Assessments before and after treatment were performed (photography, ultrasound, and thermography). Quantitative data were tabulated for statistical analysis. The images were analyzed qualitatively. The use of pants made of long-infrared (IVL) emitting fabric, under the experimental conditions presented, was shown to promote a slight reduction in edema and a significant decrease in surface temperature. These effects resulted in a qualitative improvement in the appearance of skin changes, including skin texture and the depth of depressions. Preliminary results indicate that this technology may be a promising therapeutic strategy in the treatment of cellulite.